Cannabis use and Drug Related Problems among Adolescents in 27 European Countries: The Utility of the Prevention Paradox. Issue 4 (August 2014) - Romelsjö, Anders; Danielsson, Anna-Karin; Wennberg, Peter; Hibell, Björn
Aims: To study the prevalence of cannabis use and drug-related problems among European adolescents and the utility of the prevention paradox. Methods: Survey data from the European School Survey Project on Alcohol and Other Drugs (ESPAD) in 2007 in the 27 countries with information about drug use and drug-related problems was used. We analysed the proportion of all drug-related problems that occurred in a high risk group and among others who had used cannabis in the previous 12 months. The cut-off for the high risk group was chosen to include 10-15 % of the most frequent cannabis users. Results: The high risk groups accounted for a substantial, but a minority, of drug-related problems among boys as well as girls. A minority of those who had used cannabis reported any drug-related problem. The proportion of adolescents with drug-related problems and the average number of problems increased with frequency of cannabis use. Conclusions: We find support for policy measures of more general character, supported by the prevention paradox. However, this does not exclude a policy supporting frequent drug users if they can be identified